Ecological validity of virtual reality simulations in workstation health and safety assessment - Personeni, Gabin; Savescu, Adriana (Frontiers in Virtual Reality, 2023)
The last decade saw a rapid rise of interest in Virtual Reality (VR) technologies, driven by more mature hardware and software tools. Within the ongoing digitalization of industry, VR technologies see uses in workstation design, operator training and tele-operation. This article focuses on how VR can contribute to workstation design including health and safety assessment. VR allows the inclusion of the operator in the workstation design process, permitting evaluation of the design in a safe, interactive and immersive virtual environment. This systematic literature review aims to qualify the ecological validity of VR tools and identify the current obstacles to safe and successful workstation design transfer. A standard systematic literature review procedure is used, on a wide selection of experimental research articles studying the validity of VR, within or outside of industrial contexts. We aggregate results from fundamental research on VR ecological validity regarding user perceptions, movement, cognition and stress. These results are discussed with respect to their influence on workstation OSH assessment in VR. Furthermore, we identify current technological factors and upcoming developments that mediate the validity of VR assessments.